The Impact of E-SPT, E-Filing, E-Billing, and Taxpayer Attitude Toward Tax Compliance on Individual Taxpayers of Micro, Small, and Medium Business in Surabaya - Adhityawati Kusumawardhani; Jessica Jennie Laurianto; Evelyn Antonia Santoso (International Journal of Organizational Behavior and Policy, 2023)
The purpose of this study is to examine the conceptual framework of the influence of e-SPT, e-Filing, e-Billing, and Taxpayer Attitudes towards Tax Compliance on Micro, Small, and Medium Enterprise (MSMEs) Taxpayers in Surabaya. The quantitative research method used is a survey with stratified sampling. The survey was given to 241 private MSME owners in Surabaya, and the data were analyzed with multiple regression in SPSS. This study shows that e-SPT, e-Filing, e-Billing, and Taxpayer Attitudes have a significant effect on Tax Compliance. This investigation may enhance the effectiveness and efficiency of the current electronic method for tax payments. In addition, this study supports the theory of planned behavior, which suggests that when taxpayers believe they are producing positive results, they will behave obediently, and the technology acceptance model, which states that acceptance of an information technology will explain taxpayer attitudes toward accepting information technology (e.g. -SPT, e-Filing and e-Billing).